(2 + √3) ² =
(2√3 + 1) ² =
(3-√3 ) (√3 + 2) ² =
(3√2-1) ² =
(√3 + 5) (5-√3) =
(2-√2) ² =
(1 + √3) (1 -3) =
(2√2-3)=
Utilizator anonim:
(2√2-3)^2 nu
Răspunsuri la întrebare
Răspuns de
1
(2 + √3) ² = 4+4√3+3 = 7+4√3
(2√3 + 1) ² = 12+4√3+1 = 13+4√3
(3-√3 ) (√3 + 2) ² = (3-√3)(3+4√3+4)=(3-√3)(7+4√3)=21+12√3-7√3-12=9+5√3
(3√2-1) ² =18-6√2+1=19-6√2
(√3 + 5) (5-√3) = (5+√3)(5-√3)=25-3=22
(2-√2) ² = 4-4√2+2=6-4√2
(1 + √3) (1 -3) =(1+√3)*(-2)=-2-2√3
(2√2-3)²= 8-12√2+9=17-12√2
Daca aici (1 + √3) (1 -3) este (1+√3)(1-√3)=1-3=-2
(2√3 + 1) ² = 12+4√3+1 = 13+4√3
(3-√3 ) (√3 + 2) ² = (3-√3)(3+4√3+4)=(3-√3)(7+4√3)=21+12√3-7√3-12=9+5√3
(3√2-1) ² =18-6√2+1=19-6√2
(√3 + 5) (5-√3) = (5+√3)(5-√3)=25-3=22
(2-√2) ² = 4-4√2+2=6-4√2
(1 + √3) (1 -3) =(1+√3)*(-2)=-2-2√3
(2√2-3)²= 8-12√2+9=17-12√2
Daca aici (1 + √3) (1 -3) este (1+√3)(1-√3)=1-3=-2
Alte întrebări interesante
Biologie,
8 ani în urmă
Matematică,
8 ani în urmă
Chimie,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă